Production Cost Control using Activity-Based Costing Methods in Information Systems - Suparto Darudiato; Yunus Widjaja (University of Respati Yogyakarta, Indonesia, 2022)
Companies engaged in furniture manufacturing with marketing targets mostly abroad are faced with very tight price and quality competition that requires a more accurate production costing system than traditional methods, which are still widely used in Indonesia. In general, companies use cost calculation methods that pay attention to only one cost driver, resulting in deviations in the calculation of actual production costs. A production cost calculation method is proposed using activity-based costing to overcome this problem. Many companies have used this method in developed countries, showing improvements in calculating production costs. The activity-based calculation method takes into account the activities that are cost drivers and is taken into account in obtaining actual production costs. So that the cost planning for the management is better, in this study, calculations using traditional methods are shown, and the results are compared with the results of the activity-based costing (ABC) method. Then an analysis of the system needed for applying the information system-based ABC method and the proposed implementation is also carried out. The information system will help calculate costs faster and more accurately.